Polluted Morality: Air Pollution Predicts Criminal Activity and Unethical Behavior - Lu, Jackson G.; Lee, Julia J.; Gino, Francesca; Galinsky, Adam D. (Psychological Science, 2018)
Air pollution is a serious problem that affects billions of people globally. Although the environmental and health costs of air pollution are well known, the present research investigates its ethical costs. We propose that air pollution can increase criminal and unethical behavior by increasing anxiety. Analyses of a 9-year panel of 9,360 U.S. cities found that air pollution predicted six major categories of crime; these analyses accounted for a comprehensive set of control variables (e.g., city and year fixed effects, population, law enforcement) and survived various robustness checks (e.g., balanced panel, nonparametric bootstrapped standard errors). Three subsequent experiments involving American and Indian participants established the causal effect of psychologically experiencing a polluted (vs. clean) environment on unethical behavior. Consistent with our theoretical perspective, results revealed that anxiety mediated this effect. Air pollution not only corrupts people’s health, but also can contaminate their morality.